Volume 1: 15th International Conference on Advanced Vehicle Technologies; 10th International Conference on Design Education; 7t 2013
DOI: 10.1115/detc2013-13165
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Product Archaeology as a Platform for Contextualizing Engineering Design

Abstract: Many engineering departments struggle to meet “the broad education necessary to understand the impact of engineering solutions in a global, economic, environmental, and societal context” (Outcome h) that is required for ABET. As a result, engineering students receive meaningful contextual experiences in piecemeal fashion and graduate with a lack of concrete competencies that bridge knowledge and practice in the global world in which they will live and work. By considering products as designed artifacts with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Given the goals of the program and the opportunity for curricular innovation within STEP, we developed a 5-week project-based learning course rooted in product archaeology. Product archaeology is a teaching framework that expands on traditional product dissection approaches and provides a space for students to explore the broader impacts of engineering design (Kemper Lewis et al, 2013). In addition to taking apart a product and examining its functions, product archaeology also provides spaces for students to explore the global, societal, economic, and environmental impacts of a particular product design.…”
Section: Product Archaeology: Vessel For Critical Pedagogymentioning
confidence: 99%
“…Given the goals of the program and the opportunity for curricular innovation within STEP, we developed a 5-week project-based learning course rooted in product archaeology. Product archaeology is a teaching framework that expands on traditional product dissection approaches and provides a space for students to explore the broader impacts of engineering design (Kemper Lewis et al, 2013). In addition to taking apart a product and examining its functions, product archaeology also provides spaces for students to explore the global, societal, economic, and environmental impacts of a particular product design.…”
Section: Product Archaeology: Vessel For Critical Pedagogymentioning
confidence: 99%
“…Techniques, such as product dissection, are being introduced in universities as state-of-the-art [42,43]. Additionally, dedicated capstone and cornerstone design courses remain the primary modes of design education [43,44] and designettes offer opportunities to expand upon these advances. The examples in this section provide inspiration for the development of the designettes framework (Sec.…”
Section: Prior Artmentioning
confidence: 99%
“…Studies in engineering education have identified and investigated several local educational contextual factors affecting design. The structure of the project (Moore, Diefes-Dux, & Imbrie, 2005), external support from faculty or clients, content knowledge, and the team context can influence student engineering design (Lewis et al, 2014;Carberry, Lee, & Ohland, 2010). Although these studies have looked at various factors, they have not attempted to look comprehensively at how the students' context constrains their design practices and what, within their context, are the salient, or important, factors that shape their designs.…”
mentioning
confidence: 99%